Free H‐Bonding Interaction Sites in Rigid‐Chain Polymers and Their Filling Approach: A Molecular Dynamics Simulation Study. Issue 6 (21st April 2021) - Yang, Cheng; Xu, Ruopei; Tang, Siyi; Zhuang, Yongbing; Luo, Longbo; Liu, Xiangyang
Abstract: Hydrogen bond (H‐bond) plays an important role in structure evolution and properties of various polymers. Due to directivity and saturation of H‐bond, its formation is influenced by macromolecular chain conformation but the relationship is still not well understood up to now. In this paper, amorphous models of polyamide 66 (PA66), polyamide 6T (PA6T), and poly( p ‐phenylene‐terephthamide) (PPTA) are built to study influence of chain rigidity on H‐bonding formation by utilizing Molecular Dynamics simulation. Compared with PA66 and PA6T, it is found that chain rigidity of PPTA is more remarkable and corresponding conformation adjustment is hindered more significantly, which leads to considerable weak H‐bonds and free H‐bonding sites. After introducing benzimidazole moiety into PPTA, more H‐bonds form due to more potential H‐bonding sites in benzimidazole units. However, the newly added H‐bonding donor and acceptor are in the co‐ring, and there is a high rotational energy barrier for benzimidazole ring, both of which hinder the formation of strong H‐bonds. Therefore, a strategy is proposed to fill free H‐bonding sites in rigid‐chain polymers through adding oligomers with high movement ability. Thus, the H‐bonds in rigid‐chain polymers are effectively enhanced due to bridging effect of oligomers and tensile modulus of the aramid is improved significantly. Abstract : The formation mechanism of free H‐bonding sites between rigid chains is explored by Molecular Dynamics simulation. The conformation adjustment of rigid chain is hindered due to large chain rigidity and high energy barrier. Oligomers possessing strong ability in chain movement are added in rigid‐chain polymers and thus H‐bonding strength is enhanced by bridging effect of oligomers.